The Glorification of the Son of Man: An Analysis of John 13:31-32 - Peter Ensor (Tyndale Bulletin, 2007)
The article examines the textual, exegetical and historical questions surrounding John 13:31-32. Accepting the Nestle-Aland text as it stands, the article argues that Jesus is represented as saying, at least in part, that through his return to the Father by way of the cross his divine qualities would be revealed, that he would thereby fulfil the role of the ‘one like a son of man’ of Daniel 7:13-14, and that God’s own divine qualities would also thereby be revealed. These motifs, it is argued, may be traced back to the historical Jesus and may even have been expressed in the context of the Last Supper, where John places them.